Application of machine learning and knowledge-based systems to support decision-making on fate and behaviour of engineered nanoparticles in aqueous environment - Daramola, Michael Olawale (University of Pretoria, 2025)
Thesis (PhD (Chemical Engineering))--University of Pretoria, 2025.